ASPECTOS DA PRODUÇÃO DE AFILHOS EM CANA-DE-AÇÚCAR - Santos, Cleverson D. d.; Kruger, Cleusa a. M. B.; Silva, Jose A. G. d.; Silva, Adair J. d.; Brendler, João; Carollo, Alex; Gaviraghi, Juliano; Fontaniva, Cristiano; Schiavo, Jordana; Arenhardt, Emílio G. (Salão do Conhecimento, 2013)
Resumo